Existing Human factors Risks in Eastern Africa Aviation Operation: Focus on skill Risks and Aeromedical factors. A Cross-sectional Study. - Nassimbwa, Florence; Twesigye, Charles K.; Asio, Santa M. (Student's Journal of Health Research Africa, 2022)
Background: Aviation safety in the Africa region has continued to be a concern for the International Civil Aviation Organization (ICAO) and the industry as a whole. ICAO’s 2012 accident statistics show that Africa had an accident rate of 5.3 per one million departures with 3% of the worldwide traffic distribution. A study set out to examine the existing human factors risks in the region’s aviation operation with a particular focus on skill and aeromedical risks exist in the Eastern African region. Methodology: A cross-sectional study research design was used with quantitative methods of data collection applied; perceptual information was collected by the use of a survey. Results: Four categories of variables investigated skills required for the job and had a positive moderately strong correlation with values between 0.4-0.6 and were statistically significant with p ˂0.05. Another four had a weak positive correlation which is less than 0.4. Eleven out of fifteen categories of the aeromedical variables had a positive moderately strong correlation with values between 0.4-0.6. Four had a weak positive correlation which was less than 0.4. Results did show current skill-related risks in public safety, operations monitoring, quality control, troubleshooting, design and telecommunications, and public safety. Most of the above skills had a direct correlation with each other. Conclusions: Aeromedical factors affecting performance included fitness and health, stress, time pressure, and deadlines, sleep-related issues, fatigue, cigarette smoking, alcohol, pain, and nervousness. Recommendations: There is a need for redefining human factors risks in Eastern Africa and incorporating them in the curriculum at all levels to ensure that individuals are capable of functioning effectively and safely in a range of situations and environments continuous as well as aeromedical assessment should be designed to fully capture the existing skill related and aeromedical risks in the region and improve the region’s safety record.